Making their mark art by women in the Shah Garg Collection - Godfrey, Mark 19XX-; Siegel, Katy 1966-; Belasco, Daniel 1975-; Adamson, Glenn 1972-; Getsy, David 1973-; Bell, Kirsty 1971-; Brown, Jessica Bell; Sutton, Gloria (Gregory R. Miller & Co., 2023)
This book explores the bold vision and vast range of achievements of women artists working predominantly across North America from the late 1960s into the present moment. The paintings, sculpture and mixed-media works featured are drawn from the Shah Garg Collection, which is dedicated to illuminating the critical role that women have played in shaping the development of abstraction and the narratives of art more broadly. Making Their Mark includes two sweeping essays by editors Mark Godfrey and Katy Siegel, writings by six scholars on topics relevant to the depth of the collection, such as the importance of craft traditions, artistic experimentation with new technologies and the impact of personal and communal identity on artmaking, as well as lively texts by 15 artists about the artists who inspire them. Richly illustrated with works by 136 artists, this volume offers new insights that make it a resource for students of art and general readers alike. Artists include: Pacita Abad, Candida Alvarez, Olga de Amaral, Emma Amos, Firelei Báez, Jennifer Bartlett, Barbara Chase-Riboud, Trude Guermonprez, Jacqueline Humphries, Suzanne Jackson, Maria Lassnig, Simone Leigh, Julie Mehretu, Joan Mitchell, Senga Nengudi, Toyin Ojih Odutula, Calida Rawles, Ilana Savdie, Tschabalala Self, Lorna Simpson, Jaune Quick-to-See Smith, Pat Steir, Lenore Tawney, Toshiko Takaezu, Charline von Heyl, Kay WalkingStick and Mary Weatherford
Keywords: Shah, Komal; Garg, Gaurav; Geschichte 1970-2022; Sammlung; Frauenkunst